(untitled) (New York, 1995)
This innovative reader begins with broad thematic chapters on topics and then breaks them down into clusters of 3 or 4 readings called "constellations" on more provocative, even controversial, issues. These "constellations" put the readings in a more specific context to encourage students to compare them for differing perspectives and rhetorical strategies
Keywords: College readers,Report writing,English language; Problems, exercises, etc.,Rhetoric